Click Synthesis of 5-Substituted 1H-Tetrazoles from Aldehydes, Hydroxylamine, and [bmim]N3 via One-Pot, Three-Component Reaction - Heravi, Majid M.; Fazeli, Azadeh; Oskooie, Hossein A.; Beheshtiha, Yahya S.; Valizadeh, Hassan (Synlett, 2012)
An easy and efficient one-pot, three-component method for the synthesis of 5-substituted 1H-tetrazole derivatives, via the reaction of aldehydes, hydroxylamine, and [bmim]N3, is reported.
Keywords: 5-substituted 1H-tetrazoles; three-component; click reaction; cyclization; aldehydes; 1-butyl-3-methylimidazolium azide